On-line cursive handwriting recognition: a survey of methods and performances - Mohamad, Dzulkifli; Zafar, Muhammad Faisal; Othman, Muhamad Razib (-, 2012)
This paper presents a detailed review of prior techniques and applications for on-line cursive handwriting recognition. This survey is divided into two parts, the first one dealing with the review of main approaches used in character recognition, since most have been used in cursive script recognition as well. The second one is focusing on the prior techniques for on-line cursive handwriting recognition and their applications.